ACTUALIZATION OF NATIONAL DEFENSE ATTITUDES IN THE CONTEXT OF COVID-19 HEALTH PROTOCOL AWARENESS - Ardani; Dinar Sugiana Fitrayadi; Febrian Alwan Bahrudin (Journal Civics And Social Studies, 2022)
The Covid-19 pandemic not only has an impact on health, but other sectors are also affected by the outbreak of Covid-19. The Covid-19 pandemic will become a complex problem for the country if it is prolonged and not handled properly. This research aims to find out how the actualization of the state defense attitude is in the context of awareness of implementing the Covid-19 health protocol among the community in the Pasar Rau area of ​​Serang City, Banten Province. The approach used in this research is a qualitative approach with descriptive methods, data is collected through observation, interviews and documentation techniques. The research results show that understanding and awareness regarding the implementation of the Covid-19 health protocol rules as a form of state defense carried out by the community is still low, due to low literacy regarding Covid-19 prevention plus the existence of wrong views about Covid-19. Efforts are needed from the Serang City government and also the community to overcome the dangers of Covid-19, while there are still obstacles faced by the community in implementing health protocol rules. During the Covid-19 pandemic conditions, the public can actualize efforts to defend the country by having the understanding and awareness to prevent Covid-19, because defending the country covers a wide range of things in the life of the nation and state. The government and society must work together to overcome and deal with the Covid-19 pandemic. Good public understanding and awareness in preventing Covid-19 can minimize the occurrence of Covid-19 infection and reduce the impact caused by Covid-19.